Pengaruh Gaya Hidup terhadap Hipertensi pada Remaja: Literature Review - Diana, Tyra Septi; Hastono, Sutanto Priyo (Faletehan Health Journal, 2023)
Nowadays, hypertension was mostly suffered by people in developed countries and became one of silent killer illnesses since it does not show any symptoms. The disease was mostly found in adolescents with risk factors, such as lack of sleep duration, low physical activity, poor diet, alcohol consumption, and smoking behavior. The purpose of this study was to determine lifestyle factors that influence the incidence of hypertension in adolescents. The research method was literature review using several databases, namely: Garuda Portal, Google Scholar, and ScienceDirect and the publications were from 2018 to 2022. The researcher obtained 9 articles relating to inclusion criteria and exclusion criteria. The results of this literature review showed that lifestyle factors affecting the incidence of hypertension in adolescents are physical activity, smoking behavior, alcohol consumption, sleep duration, and poor diet (fat intakes).